The influence of extrusion ratio on contact stresses and die elastic deformations in the case of cold backward extrusion - Pepelnjak, Tomaž (Strojniški vestnik, 2016)
In this paper, the distribution of contact stresses along the die-workpiece interface as well as elastic deformation behavior of the die in the cold backward extrusion of steel billets have been investigated both experimentally and numerically. For the experiments, a special tooling set including a pin load cell measuring device was designed and made. Contact stresses were recorded at various points in time and at various locations during the extrusion process, i.e. for different punch strokes (part's bottom thickness). The research focus was on determining the extrusion ratio's influence on the distribution of the contact stresses and therefore the experiments were performed using five punches of different head diameters. In the next step, based on the measured contact stresses, radial displacements of the inner die wall were calculated by applying Lame's equation. Furthermore, an extended finite element analysis of the investigated extrusion process was carried out using Simufact.forming software. The results of numerical simulations for the contact stresses were compared with experiments. The benefits and weaknesses of the pin load cell measuring technique and Lame's formula when it is employed for determination of the die elastic deformation were also examined, as well as were the contribution of the die elastic deformation to dimensional errors of the extruded parts.
Keywords: elastična deformacija matrice; finite element method; kontaktne napetosti; metoda končnih elementov; palična tlačna merilna celica; protismerno iztiskavanje